Refraction and reflection of bulk spin waves on a boundary of two homogeneous dielectric ferromagnets having biaxial anisotropy - Gorobets, Yu.I.; Reshetnyak, S.A. (Functional Materials, 2004)
Refraction index of spin waves propagating in a dielectric ferromagnetic medium consisting of two homogeneous parts with different parameters of exchange interaction, uniaxial and rhombic anisotropy as well as saturation magnetization, has been calculated in the formalism of spin density, taking into account the defect of exchange interaction on the interface of this media. The coefficients of spin wave reflection and transmission have been computed. The dependences of both reflected wave intensity and refraction index on the wave frequency and value of external permanent homogeneous magnetic field have been obtained.